Korean Diaspora in the South Korean media discourse: changing narrative. Issue 2 (2nd July 2020) - Gorbunova, Ekaterina
ABSTRACT: This paper aims to analyse the perception of Koreans overseas in South Korean mass media. Nowadays, due to globalization processes, the economic, political and cultural contacts between South Korean society and Korean diaspora has intensified. As a result, the perception of Korean immigrants in South Korea is becoming more positive. The analyses of media materials show that South Korean media highly estimate the contribution made by Korean immigrants to the development of South Korea, both historically and in the modern period. In addition, media also praise the positive qualities of Korean immigrants, such as being hardworking, and their active participation in the political and economic life of the host country. Another common narrative is the positive role of Korean diaspora in bilateral relations between the host country and South Korea. The comparison of recent media materials with those of the beginning of the XXI century shows that the positive representation of Korean diaspora is a recent tendency. The article also underlines that the way South Korean media develop a narrative about South Korean diaspora is on many occasions close to the narrative of South Korean officials.